COMPLIANCE CULTURE IN A LARGE COMPANY: INTERVENTION PROPOSAL - Cicero da Silva, Luciano; de Oliveira Francklin, Bruna; Matteus Oliveira Souza, Igor; Cristina de Oliveira Bagnarelli, Jéssica; Eduarda de Lima Ferreira, Maria (Revista Gênero e Interdisciplinaridade, 2023)
This article proposes an intervention for a large company located in the interior of São Paulo – SP, where the topic addressed is compliance with an anti-bribery management system and the importance of implementing ISO 37001. Compliance aims to minimize risks and guide the company’s behavior in the market in which it operates. It is an internal control system that clarifies and offers security to those who use it. ISO 37001 is a compliance and anti-bribery management system that aligns strategies and processes. Based on this, we conclude the importance of ISO 37001, and how much it adds to the company’s image, improving its reputation.